2010
DOI: 10.1007/s11274-010-0427-2
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungal community structure and diversity in response to long-term fertilization: a field case from China

Abstract: The influences of different fertilizer treatments on spore community structure and diversity of arbuscular mycorrhizal (AM) fungi (AMF) were investigated in a long-term fertilization experiment with seven treatments: organic manure (OM), half organic manure N plus half fertilizer N (1/2 OMN), fertilizer NPK, fertilizer NP, fertilizer NK, fertilizer PK, and the control (without fertilization). Fertilization generally increased the nutrient contained in the fertilizer and treatments with NPK and 1/2 OMN produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 36 publications
(51 reference statements)
2
20
2
Order By: Relevance
“…A total of 30 AM fungal species was recorded in this study, slightly lower than the number of 35 reported from the same arable land (Wang et al, 2011a). The genus Acaulospora registered the largest species number, while Acaulospora denticulata was the most abundant species with a relative abundance (RA) of 21.8-25.1% (Table 3).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…A total of 30 AM fungal species was recorded in this study, slightly lower than the number of 35 reported from the same arable land (Wang et al, 2011a). The genus Acaulospora registered the largest species number, while Acaulospora denticulata was the most abundant species with a relative abundance (RA) of 21.8-25.1% (Table 3).…”
Section: Discussioncontrasting
confidence: 52%
“…previous studies (Wang et al, 2011a;Yang et al, 2011). Spore specimens identified to species were used in the analysis of the relative abundance (RA) and the species richness (SR).…”
Section: Parametersmentioning
confidence: 99%
“…Therefore, some of these PLFAs identified in fungi especially in limed sites, might be from plant materials. In general, 16:1ω5 and 18:1ω7 are good indictors of AM fungi [41,42]. Both PLFAs were slightly more abundant in limed sites compared to unlimed samples.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies report lower AMF species richness because of N (Egerton-Warburton et al, 2007;Wang et al, 2011) and also P fertilization (Alguacil et al, 2010;Gosling et al, 2013). Previous studies report lower AMF species richness because of N (Egerton-Warburton et al, 2007;Wang et al, 2011) and also P fertilization (Alguacil et al, 2010;Gosling et al, 2013).…”
Section: Introductionmentioning
confidence: 92%